The safety of emergency medicine. Issue 4 (3rd November 2015) - Ramlakhan, Shammi; Qayyum, Hasan; Burke, Derek; Brown, Ruth
Abstract : The patient safety movement has been active for over a decade, but the issue of patient safety in emergency care and the emergency department (ED) has only recently been brought into the forefront. The ED environment has traditionally been considered unsafe, but there is little data to support this assertion. This paper reviews the literature on patient safety and highlights the challenges associated with using the current evidence base to inform practice due to the variability in methods of measuring safety. Studies looking at safety in the ED report low rates for adverse events ranging from 3.6 to 32.6 events per 1000 attendances. The wide variation in reported rates on adverse events reflects the significant differences in methods of reporting and classifying safety incidents and harm between departments; standardisation in the ED context is urgently required to allow comparisons to be made between departments and to quantify the impact of specific interventions. We outline the key factors in emergency care which may hinder the provision of safer care and consider solutions which have evolved or been proposed to identify and mitigate against harm. Interventions such as team training, telephone follow-up, ED pharmacist interventions and rounding, all show some evidence of improving safety in the ED. We further highlight the need for a collaborative whole system approach as almost half of safety incidents in the ED are attributable to external factors, particularly those related to information flow, crowding, demand and boarding.